الخصائص الريادية لأصحاب الأعمال الصناعية الصغيرة وأثرها على الاداء دراسة تطبيقية على الاعمال الصناعية الصغيرة في الاردن - الضامن، رولا علي عبدالله (جامعة المنصورة - كلية التجارة, 2012)
هدفت الدراسة إلى قياس أثر الخصائص الريادية (القدرات الإبداعية، والابتكار، والدافع للإنجاز، والميل إلى المخاطرة، والمبادأة) لصاحب العمل الصناعي الصغير على أداء العمل. تكون مجتمع الدراسة من جميع مشروعات الأعمال الصناعية الصغيرة العاملة في العاصمة عمان. تم اختيار عينة عشوائية طبقية نسبية من الأعمال الصناعية الصغيرة في العاصمة عمان ليبلغ مجموع أفراد العينة (311) مشروعًا صغيرًا. أظهرت نتائج الدراسة إلى وجود أثر ذو دلالة إحصائية للخصائص الريادية مجتمعة في أداء الأعمال الصناعية الصغيرة العاملة في العاصمة عمان. ووجود أثر ذو دلالة احصائية للخصائص الريادية منفردة على أداء الأعمال الصناعية الصغيرة. كما أظهرت النتائج وجود فروق ذات دلالة إحصائية في الخصائص الريادية وفقًا للمتغيرات (الجنس، العمر، المؤهل العلمي، والخبرة الوظيفية). تم تقديم مجموعة من التوصيات التي هدفت إلى تشجيع أصحاب العمل العاملين لديهم على تطوير الخصائص الريادية لما له من أثر إيجابي في تحسين أداء الأعمال الصناعية الصغيرة. The study aims at investigating the effect of entrepreneurial characteristics (represented by: innovation competencies, creativity, initiation, risk tasking and need for achievement) on the performance of small industrial businesses in Jordan. The population of the study consisted of all small industrial businesses in capital Amman,. A stratified, percentile sample was selected from small industrial businesses totaling 311 projects. The results indicated a significant effect for thecombined entrepreneurial characteristics was found in the performance of small industrial businesses in Amman. And a significant effect for the individual entrepreneurial characteristucs (represented by: innovation competencies, creativ initiation, risk tasking and need for achievement) was found in small industn d businesses performance. Also results show that there were a statistical differences at (0.05) level for each of (age of the owner, Sex, education level, and experience) on entrepreneurial characteristics. The study recommended the owners of small industrial businesses to concentrate on the development of their entrepreneurial characteristics which has positive effect on the performance of the small industrial businesses.
810201
Keywords: الابتكار -- الصناعات الصغيرة -- الاردن -- التنمية الاقتصادية -- القيادة الادارية -- تقييم الاداء -- المخاطرة -- الرضا الوظيفي -- الربحية